2001
DOI: 10.1515/znb-2001-1215
|View full text |Cite
|
Sign up to set email alerts
|

The Gold Sulfates MAu(S04)2 (M = Na, K, Rb)

Abstract: The evaporation of a solution of Au(OH)3 and Na2SC>4 in conc. sulfuric acid led to yellow single crystals of NaAu(S04)2 (monoclinic, P2\/n, Z = 2, a = 469.1, b = 845.9, c = 831.2 pm, ß = 95.7°). Analogous procedures with K2SO4 or Rb2SC>4 instead of Na2SC>4 yielded single crystals of KAu(SC>4)2 (monoclinic, Cite, Z = 4, a = 1109.8, b = 724.2, c = 941.1 pm, ß = 118.4°) and RbAu(S04)2, respectively, (triclinic, PI, Z -1, a = 423.6, b -497.5, c = 889.0 pm, a = 76.4°, ß = 88.4°, 7 = 73.5°). Although the crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…For the anhydrous sodium rare-earth metal oxosulfates NaRE[SO 4 ] 2 , their monoclinic crystal structure was solved in space group P2 1 /m for RE = Er [31] and Tm [32] and the triclinic one in space group P1 for RE = La [33] and Nd [31]. For trivalent gold instead of RE 3+ cations, the monoclinic crystal structure of NaAu[SO 4 ] 2 was described in space group P2 1 /n [34], but Au 3+ in square planar oxygen coordination causes marked topological differences. Not so different from the Na + analogs, for triclinic AgEu[SO 4 ] 2 (space group: P1) with Ag + in eightfold oxygen coordination, its Eu 3+ bulk luminescence was also measured very recently [35].…”
Section: Introductionmentioning
confidence: 99%
“…For the anhydrous sodium rare-earth metal oxosulfates NaRE[SO 4 ] 2 , their monoclinic crystal structure was solved in space group P2 1 /m for RE = Er [31] and Tm [32] and the triclinic one in space group P1 for RE = La [33] and Nd [31]. For trivalent gold instead of RE 3+ cations, the monoclinic crystal structure of NaAu[SO 4 ] 2 was described in space group P2 1 /n [34], but Au 3+ in square planar oxygen coordination causes marked topological differences. Not so different from the Na + analogs, for triclinic AgEu[SO 4 ] 2 (space group: P1) with Ag + in eightfold oxygen coordination, its Eu 3+ bulk luminescence was also measured very recently [35].…”
Section: Introductionmentioning
confidence: 99%
“…RbAu(SeO 4 ) 2 crystallizes monoclinically with the space group C2/m and is not isotypic with one of the respective sulfates known so far [7,8]. However, the main structural feature of RbAu(SeO 4 ) 2 , [AuO 4 ] units linked by tetrahedral anions to infinite chains 1 ϱ [Au-(SeO 4 ) 4/2 ] Ϫ , is almost the same as found for MAu(SO 4 ) 2 (M ϭ Na-Rb) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately the latter have not been characterized structurally. We recently showed that in the structure of the respective ternary sulfates MAu(SO 4 ) 2 (M ϭ Na-Rb) square planar [AuO 4 ] units are linked to chains according 1 ϱ [Au(SO 4 ) 4/2 ] Ϫ while for CsAu(SO 4 ) 2 a connection of these units to layers was observed [7,8]. We now started to investigate also the selenates structurally and we here present the crystal structure of the first ternary gold selenate which is surprisingly not isotypic with one of the sulfates.…”
mentioning
confidence: 99%